PENGARUH ESG SCORE, TAX AVOIDANCE, DAN TRANSFORMASI DIGITAL TERHADAP VOLATILITAS HARGA SAHAM. - Nimas Ichsanti; Rosiyana Dewi (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2026)
This study examines the effects of ESG performance, tax avoidance, proxied by the effective tax rate (ETR), and digital transformation on stock price volatility among energy sector companies listed on the Indonesia Stock Exchange during 2022–2024. Using a quantitative approach, panel data regression, and purposive sampling, the study obtained 135 firm-year observations. ESG data were sourced from Bloomberg, while financial and stock market data were collected from annual reports, sustainability reports, and Yahoo Finance. Model selection was conducted using the Chow, Hausman, and Lagrange Multiplier tests, resulting in the Fixed Effect Model. The results show that ESG performance positively and significantly affects stock price volatility, suggesting that stronger ESG performance may increase market sensitivity. ETR negatively and significantly affects volatility, indicating that greater tax compliance reduces market uncertainty. Digital transformation positively and significantly affects volatility because digital initiatives create growth expectations and implementation risks. These findings enrich energy-sector volatility literature.